2022
DOI: 10.1111/andr.13189
|View full text |Cite
|
Sign up to set email alerts
|

Hematospermia is rarely associated with urologic malignancy: Analysis of United States claims data

Abstract: Background: Hematospermia is an alarming symptom and can cause significant patient distress, but work-up is often negative.Objective: To characterize the clinical evaluation of hematospermia and its association with the diagnosis of urologic malignancy. Materials and methods:Using MarketScan insurance claims database, we identified adult males 18-64 years old diagnosed with hematospermia from 2010 to 2018. Benign hematospermia was defined as the absence of hematuria and elevated prostate-specific antigen. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
2
0
0
Order By: Relevance
“…Nevertheless, recent insurance data from the United States report an incidence of 73.6 per 100,000 in 2018, with 0.08% of cases attributable to urological cancer. 2 This finding is consistent with another study that reported on a large prostate cancer screening population (n = 26,126) in which hematospermia was found to be 0.5%. 3 In a recent meta-analysis of a total of 20 studies, the etiology of hematospermia remained unknown in 52% of cases.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, recent insurance data from the United States report an incidence of 73.6 per 100,000 in 2018, with 0.08% of cases attributable to urological cancer. 2 This finding is consistent with another study that reported on a large prostate cancer screening population (n = 26,126) in which hematospermia was found to be 0.5%. 3 In a recent meta-analysis of a total of 20 studies, the etiology of hematospermia remained unknown in 52% of cases.…”
Section: Introductionsupporting
confidence: 92%
“…The incidence of hematospermia is quite unclear, as most ejaculations during sexual intercourse go unnoticed. Nevertheless, recent insurance data from the United States report an incidence of 73.6 per 100,000 in 2018, with 0.08% of cases attributable to urological cancer 2 . This finding is consistent with another study that reported on a large prostate cancer screening population ( n = 26,126) in which hematospermia was found to be 0.5% 3 .…”
Section: Introductionsupporting
confidence: 88%